Morphometry of the stone crayfish (Austropotamobius torrentium) in the Czech Republic: allometry and sexual dimorphism - Vlach P.; Valdmanová L. (Knowledge and Management of Aquatic Ecosystems, 2015)
The stone crayfish Austropotamobius torrentium (Schrank, 1803) is a native crayfish species in the Czech Republic. Biometric analysis of this crayfish species in the Czech Republic has not been performed up to now. The aim of this paper is to provide these data. The maximum observed body length was 94.8 mm in females and 103.6 mm in males. As the main characters of sexual dimorphism were observed, males had the carapace and chelae relatively longer in relation to the total body length and the carapace length respectively, while females showed longer rostro-cervical part of the carapace and wider abdomen. The chelae width/length ratio was larger in females; the chelae width/length ratios and abdomen width differed between sexes in both adults and juveniles. Most of observed body parts grow allometrically. The positive allometry was found in the following length relations: the carapace length in males only, carapace width, and abdomen width (all related to the carapace length) in females, and chelae width/length ratio in females. Negative allometric growth was recorded in the length of the rostro-cervical part of the carapace, chelae width, and chelae height in males.